The Baltic countries sectoral share price indexes VAR model - Uzdanavičiūtė, Roma; Rudzkis, Rimantas (Lietuvos matematikos rinkinys, 2011)
According to the same modern Baltic countries economical and political integration, united OMX Baltic security market created.The main purpose of this article is to forecast her sectoral share price indexes according to their interdependent relationship during 2000-2010 year.Time series models, linear regression models and a vector autoregression model (VAR) can be used to model and forecast indexes processes.Therefore, the vector autoregression model is proposed for modelling.Theoretical aspects of model estimation are reviewed: time series stationarity, model identification, parameter estimation, model usage and forecasts.